Deregulation of Transcription Factor Networks Driving Cell Plasticity and Metastasis in Pancreatic Cancer - van Roey, Ruthger; Brabletz, Thomas; Stemmler, Marc P.; Armstark, Isabell (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer is a very aggressive disease with 5-year survival rates of less than 10%. The constantly increasing incidence and stagnant patient outcomes despite changes in treatment regimens emphasize the requirement of a better understanding of the disease mechanisms. Challenges in treating pancreatic cancer include diagnosis at already progressed disease states due to the lack of early detection methods, rapid acquisition of therapy resistance, and high metastatic competence. Pancreatic ductal adenocarcinoma, the most prevalent type of pancreatic cancer, frequently shows dominant-active mutations in KRAS and TP53 as well as inactivation of genes involved in differentiation and cell-cycle regulation (e.g. SMAD4 and CDKN2A). Besides somatic mutations, deregulated transcription factor activities strongly contribute to PDAC progression. Specifically, transcriptional regulatory networks essential for proper lineage specification and differentiation during pancreas development are reactivated or become deregulated in the context of cancer and exacerbate progression towards an aggressive phenotype. This review summarizes the recent literature on transcription factor networks and epigenetic gene regulation that plays a crucial role during PDAC tumorigenesis.